2022
DOI: 10.1111/apt.17348
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of disease activity during pregnancy in women with inflammatory bowel disease—a Danish cohort study

Abstract: Summary Background and Aims Inflammatory bowel disease (IBD) activity during pregnancy is associated with adverse pregnancy outcomes. We aimed to identify key clinical characteristics that predict disease activity during pregnancy. Methods Between January 2008 through 2021, we identified all singleton pregnancies among women with IBD recorded in patient and birth registries at a tertiary IBD centre in Denmark. Maternal and infant data were retrieved from medical records. Demographics, Physicians Global Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
10
0
6
Order By: Relevance
“…The authors of this study also found that remission at least 6 months prior to and at conception was a predictor of remission during pregnancy 8 . This is a new finding that extends the suggested time period for quiescent disease prior to pregnancy from 3 months 4,5 .…”
supporting
confidence: 73%
See 3 more Smart Citations
“…The authors of this study also found that remission at least 6 months prior to and at conception was a predictor of remission during pregnancy 8 . This is a new finding that extends the suggested time period for quiescent disease prior to pregnancy from 3 months 4,5 .…”
supporting
confidence: 73%
“…9,10 The authors of this study also found that remission at least 6 months prior to and at conception was a predictor of remission during pregnancy. 8 This is a new finding that extends the suggested time period for quiescent disease prior to pregnancy from 3 months. 4,5 A third finding was that ulcerative colitis was associated with a higher risk of flare in comparison to Crohn's disease, which has been noted in prior work.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…We thank Drs. Kane and Chowdury for their comments regarding our study on predictors of disease activity during pregnancy in women with inflammatory bowel disease (IBD) 1 …”
mentioning
confidence: 99%